Estimation of thyroid hormones and liver enzymes levels in hypo and hyperthyroidism in iraqi women - BUSHRA F. HASAN,; NOOR ALHUDAKHIBRAHIM,; DUAA A. ABD, (International Journal of Pharma and Bio Sciences, 2016)
Thyroid hormones are secreted to control tissues metabolism rate ,so that any alteration in their action will affect the system of many organs and change many enzymes level included liver enzymes aspartate amino transferase(AST), alanine amino transferase (ALT) and alkaline phosphatase (ALP) and total serum bilirubin(TSB). The study is conducted to estimate the correlation between thyroid hormones levels alteration with liver enzymes levels and lipid profile. This study includes(60) hypo and hyperthyroidism patients compared with 30 apparently healthy control group who have attended to Nursing Home Hospital in Baghdad Medical City. Thyroid hormones are measured by automated system(TOSO), while lipid profile and liver enzymes are measured by auto analyzer by (COBAS 11). Results show increase in the enzymes ALP, AST, ALT, and TSB levels in both hyper and hypothyroid ismpatients, lipid profile LDL,TG,TC levels increase in all cases, but HDL increase in hypothyroidism and decrease in hyperthyroidism patients. Thyroid hormones levels are significantly correlated with liver enzymes level and lipid profile in hyper and hypothyroidism patients (p<0.05) (p<0.01) respectively. The current study demonstrates that there is an appositive association between thyroid hormones levelsand liver enzymes levels (ALT, AST and ALP) and TSB levels.